Comparison of three methods for measuring C0-1 angles and C0-2 angles - Xu, Shicai; Ma, Fei; Tang, Chao; Liao, Yehui; Tang, Qiang; Chen, Shiyu; Wang, Qing; Zhong, Dejun (BMC musculoskeletal disorders, 2023)
The mutual compensatory relationship between the upper cervical sagittal alignment and the lower cervical sagittal alignment has been repeatedly reported. However, the evaluation of the upper cervical sagittal parameters are varied in previous studies. This retrospective study was performed to compare three methods for measuring the upper cervical sagittal parameters. A total of 263 individuals with standing neutral lateral cervical radiographs were included in this study. The Frankfort horizontal line (FHL), foramen magnum line (FML), and McGregor line (ML) were separately used as the reference lines for measuring the C0-1 angle and C0-2 angle. Intraclass correlation (ICC) values were used to compare the consistency and repeatability of the three methods. Pearson's correlation analysis was used to analyze the correlation between the sagittal parameters of the upper and lower cervical spine. The interobserver and intraobserver ICC values obtained from using the ML to measure the C0-1 angle and C0-2 angle were both higher than those obtained from using the FML or FHL. The C0-1 angle and C0-2 angle measured by the three methods were negatively correlated with the C2-7 angle. The upper sagittal parameters measured by the FHL were the most correlated with the C2-7 angle. The correlation between the C0-1 angle measured by the three methods and the C0-2 angle measured with the FHL or ML and the C2-7 angle increased with aging. Use of the ML to measure the C0-1 angle and C0-2 angle has higher reliability. Use of the FHL to measure the sagittal alignment of the upper cervical spine is more suitable for evaluating the compensation mechanism between the upper and the lower cervical spine.